The Labor Impact of Coal Phase Down Scenarios in Chile - Adrien Vogt-Schilb; Kuishuang Feng (Inter-American Development Bank, 2019)
This study explores the labour impact of four scenarios of electricity generation in Chile, including three coal power phase-down scenarios. These scenarios would result in the creation of between 32 and 40 thousand direct and indirect jobs and between US1.7 and US1.8 billion in value added in 2030, compared to present-day situation. Net numbers mask winners and losers. The most significative negative impact we find would be the progressive disappearance of 4 thousand jobs in coal power plants by 2030 or 2050 depending on the scenario. These impacts are not significant when compared to Chile's labor markets and GDP. Chile's economy routinely creates more than 40 thousand jobs per trimester, and US1.7 billion is just 0.8% of GDP, while GDP is expected to grow at least 2.5% per year between today and 2030. At the national level, our results suggest that a careful planning and implementation of coal phase out could be able to mitigate its negative impacts, given that they will be small relative to the size of Chile's economy. In practice, whether the jobs created nationally match the skills available in the geographical location of current coal power plants is likely to play a key role. This study does not investigate this issue, but a separate technical note studies affected communities with more details and provides lessons learned from historic management of the labor impacts of policy reforms.
Keywords: 330; Labor impacts; Coal phase out; Climate change; Chile; Input-output analysis; Scenario analysis; Just Transition